1997
DOI: 10.1139/g97-055
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microsatellites in Norway spruce (Picea abiesK.)

Abstract: Norway spruce (Picea abies) genomic libraries were screened for presence of dinucleotide AC/GT and AG/CT microsatellites (or simple sequence repeats). On average, one (AG)n microsatellite every 194 kb and one (AC)n microsatellite every 406 kb were found. Forty-six positive clones were sequenced and primers flanking 24 AG microsatellites and 12 AC microsatellites diesigned. Only seven (20%) of them produced the expected single-locus polymorphic pattern when used to amplify Norway spruce DNAs. The other primer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
151
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 24 publications
(22 reference statements)
12
151
2
2
Order By: Relevance
“…This supports a previous study of Norway spruce, which found that primer pairs amplifying a single polymorphic microsatellite were largely restricted to unique clone sequences that lacked repetitive DNA (Pfeiffer et al. 1997). Causes of microsatellite failure in our study included (1) PCR amplification failure, which resulted either in no discernible product or in a small number of nonspecific bands; (2) the amplification of monomorphic bands resembling microsatellite alleles; or (3) the amplification of more than one locus, indicated by the presence of up to four alleles within an individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This supports a previous study of Norway spruce, which found that primer pairs amplifying a single polymorphic microsatellite were largely restricted to unique clone sequences that lacked repetitive DNA (Pfeiffer et al. 1997). Causes of microsatellite failure in our study included (1) PCR amplification failure, which resulted either in no discernible product or in a small number of nonspecific bands; (2) the amplification of monomorphic bands resembling microsatellite alleles; or (3) the amplification of more than one locus, indicated by the presence of up to four alleles within an individual.…”
Section: Discussionmentioning
confidence: 99%
“…All of these patterns have been observed in similar studies of other species with complex genomes (Pfeiffer et al. 1997; Bailie et al. 2010; McInerney et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite sequence analysis (SSR) was performed for 180 trees using the following 9 microsatellite loci: EATC1B02, EATC1E3, EATC2G05, SPAGC1, SPAGG3, EATC1G2, EATC2B02, G2 and SPAGC2 (Pfeiffer et al 1997;Scotti et al 2002). For tree genotyping, Genetic Analyzer 3500 (Life Technologies™) sequencer and Data Collection Software 3500 were used.…”
Section: Methodsmentioning
confidence: 99%
“…Four nuclear primer pairs for SSR loci were used for this study: EAC1G05, EAC1D10 (Scotti et al 2002), SpAC1B8 (Pfeiffer et al 1997), and UAPCA24 (Hodgetts et al 2001). PCR amplifications were conducted by a 96-well MasterCycler EpGradient (Eppendorf, Hauppauge, NY, USA) using a total volume of 25 μl with 2.5 μl 10 × Dream Taq Buffer, 0.5 U of Dream Taq (Termo Scientific, Fermentas, Pittsburgh, PA, USA) 200 μM dNTPs, 0.2 μM of each primer, 50 ng of total genomic DNA.…”
Section: Methodsmentioning
confidence: 99%